Early Aortic Valve Replacement versus Watchful Waiting in Asymptomatic Severe Aortic Stenosis: A Study-Level Meta-Analysis. Issue 6 (2nd November 2019) - Sá, Michel Pompeu B. O.; Cavalcanti, Luiz Rafael P.; Escorel Neto, Antônio C. A.; Perazzo, Álvaro M.; Simonato, Matheus; Clavel, Marie-Annick; Pibarot, Philippe; Lima, Ricardo C.
ABSTRACT: Background: The management of patients with asymptomatic, severe aortic stenosis (AS) is controversial. We performed a meta-analysis to examine the impact on outcomes of early aortic valve replacement (AVR) in patients with severe asymptomatic AS versus a watchful-waiting (WW) approach. Methods: Databases were searched for studies published until April 2019. Main outcome of interest was death during follow-up. Results: The search yielded 1, 889 studies for inclusion. Of these, seven articles were analyzed and their data extracted. The total number of patients included was 3, 839. The overall HR (95% CI) for death showed a statistically significant difference between the groups, with lower risk in the "early AVR" group (random effect model: HR 0.280; 95% CI 0.159–0.494, P < 0.001). There was evidence of significant statistical heterogeneity of treatment effect among the studies for death. Funnel plot analysis disclosed no asymmetry around the axis for the outcome of interest, which means that we have low risk of publication bias related to this outcome. Sensitivity analysis showed that none of the studies had a particular impact on the results. The meta-regression coefficients for the modulating factors age, male sex, presence of hypertension and presence of diabetes were significant for mortality, showing that the early intervention becomes even more protective in comparison with the conservative approach when we take these factors into consideration. Conclusion: Early AVR seems to be a better approach than WW in the treatment of asymptomatic patients with severe AS, but we would still advocate a case-by-case decision-making process.